Supplementation and fortification program in eradicating micronutrient deficiencies in Indonesia - Lestari Octavia; Johan Harlan (JKKI : Jurnal Kedokteran dan Kesehatan Indonesia, 2021)
Micronutrients play a significant role in metabolism reaction although this only needs a few micronutrients such as iron (Fe) and folic acid as folate substitutes. Fortification and supplementation program aims to meet the requirement of micronutrients by providing synthetic formula. The Indonesian government has applied iron-folic acid fortification (IFA) in flour. Moreover, the IFA supplementation program was given to vulnerable groups, pregnant mothers and women at reproductive age, including adolescent girls. The program has been applied for almost five decades, but the micronutrients deficiencies remain high. This study aims to review effects of the supplementation and fortification to vulnerable groups in Indonesia. This is necessary to  to determine their effectiveness within a specified period since the program has been applied for decades and to assess whether an additional program is needed or not. The data of this study were collected from verified international journal articles in the National Centre for Biotechnology Information (NCBI)/PubMed and Cochrane Library website. 11 articles related to the program were obtained. The program has been conducted for an extended period, yet its effectiveness should be reinforced to diminish the micronutrient deficiencies. It is mandatory to reformulate an additional program to strengthen the program. Nutrition education program, campaign for a healthy and balanced diet, protein consumption based local resources can be designated to assist the eradication of micronutrient deficiencies.